NEW CATALOG OF DISTANCES AND LIGHT CURVE PARAMETERS OF CLASSICAL CEPHEIDS - Berdnikov, L. N. (Одеські астрономічні публікації, 2017)
A new version of the catalogue of distances and light-curve parameters for galactic classical Cepheids is presented. The catalogue lists amplitudes, magnitudes at maximum light, and intensity means for 515 stars in UBVRI filters of the Johnson system and (RI)C filters of the Cron-Cousins system. The distances are based on our multicolour set of PL relations and on our Cepheid-based solution for interstellar extinction law parameters and are referred to an LMC distance modulus of 18.25.